PERSEPSI MAHASISWA BIMBINGAN KONSELING UNIVERSITAS MAHADEWA INDONESIA TERHADAP PERKULIAHAN DARING SEBAGAI SARANA PEMBELAJARAN SELAMA MASA PANDEMI COVID-19 - I Wayan Juliawan (Widyadari : Jurnal Pendidikan, 2020)
Online lectures is one form of internet utilization that can enhance the role of students in the learning process. Descriptive analysis in this study examines students' perceptions of the Mahadewa University of Indonesia on online learning models related to the use of media, learning styles, and certain types of communication that are popular with students to help them get better output from online learning activities. The number of population in this study were 126 students guidance and counseling Mahadewa University who had been involved in online learning during the Covid-19 quarantine period. The results found that the most popular online learning media are WhatsApp and Google Classroom. As many as 63,49 % of Mahadewa University students are familiar with various online learning media before online lectures begin. In addition, the communication pattern that is most popular by students is the semi-two-way pattern. Further research is needed on online learning research with problem-based, collaborative, and other models.